Overflow Analysis on the FO Purifier of KM Tanto Sukses Vessel - Bagas Sadewo; Agus Prawoto; Trisnowati Rahayu; Azis Nugroho; Nasri; Rama Syahputra; Imam Sutrisno (International Journal of Marine Engineering Innovation and Research, 2025)
This research aims to analyze the factors that cause overflow in the fuel oil purifier system and to identify measures that can be taken to address this issue using the Failure Mode and Effect Analysis (FMEA) method. Overflow in the fuel oil purifier can disrupt the fuel purification process, which is crucial for engine performance. Therefore, understanding the causes and appropriate solutions is essential. The analysis results indicate that the factors causing overflow include leakage or wear of vital components such as O-rings, gravity discs, belts, bowls, main seal rings, ball bearings, nozzles, and pilot valves, as well as improper installation of components or blockages due to debris obstructing the flow. Overflow can be managed through regular inspections of components prone to wear or damage, routine cleaning of components that are susceptible to clogging, and continuous monitoring and calibration of the system to ensure the purifier operates optimally. By implementing these measures, the fuel oil purifier system is expected to function efficiently, reduce the risk of overflow, and enhance the reliability of the fuel purification process.